The Development of Muscle Fatigue Suppresses Auditory Sensory Gating (P50) during Sustained Contraction - Aleksandrov, Aleksander A.; Dmitrieva, Elena S.; Stankevich, Ludmila N.; Knyazeva, Veronika M.; Shestakova, Anna N. (Frontiers in Systems Neuroscience, 2016)
Our aim was to study the influence of fatigue development on sensory gating during a muscle load. The fatiguing task was sustained contraction of a handgrip dynamometer with 7 and 30 % maximum voluntary contraction. The suppression of P50, an auditory event-related potential, was used as the sensory gating index in the paired-click paradigm with a 500 ms interstimulus interval; the difference between the P50 amplitudes of the first and the second stimuli of the pair was used as the sensory gating index. We found that the 30% maximum voluntary contraction fatigue development strongly decreased sensory gating, sometimes totally suppressing it. We concluded that central fatigue impaired motor performance and strongly suppressed inhibitory processes, as shown by the decreased P50 amplitude to the second stimulus. Therefore, muscle central fatigue influences sensory gating, similar to schizophrenia spectrum disorders.